Co-silencing of tomato S-adenosylhomocysteine hydrolase genes confers increased immunity against Pseudomonas syringae pv. tomato DC3000 and enhanced tolerance to drought stress - Hui, Li X.; Huang, Lei; Hong, Yongbo; Zhang, Yafen; Liu, Shixia; Juan, Zhang H.; Li, Dayong; Song, Fengming (Frontiers in Plant Science, 2015)
S-adenosylhomocysteine hydrolase (SAHH), catalyzing the reversible hydrolysis of S-adenosylhomocysteine to adenosine and homocysteine, is a key enzyme that maintain the cellular methylation potential in all organisms. We report here the biological functions of tomato SlSAHHs in stress response. The tomato genome contains three SlSAHH genes that encode SlSAHH proteins with high level of sequence identity. qRT-PCR analysis revealed that SlSAHHs responded with distinct expression induction patterns to Pseudomonas syringae pv. tomato (Pst) DC3000 and Botrytis cinerea as well as to defense signaling hormones such as salicylic acid, jasmonic acid and a precursor of ethylene. Virus-induced gene silencing-based knockdown of individual SlSAHH gene did not affect the growth performance and the response to Pst DC3000. However, co-silencing of three SlSAHH genes using a conserved sequence led to significant inhibition of vegetable growth. The SlSAHH-co-silenced plants displayed increased resistance to Pst DC3000 but did not alter the resistance to B. cinerea. Co-silencing of SlSAHHs resulted in constitutively activated defense responses including elevated SA level, upregulated expression of defense-related and PAMP-triggered immunity marker genes and increased callose deposition and H2O2 accumulation. Furthermore, the SlSAHH-co-silenced plants also exhibited enhanced drought stress tolerance although they had relatively small roots. These data demonstrate that, in addition to the functions in growth and development, SAHHs also play important roles in regulating biotic and abiotic stress responses in plants.